Peningkatan Ikatan Emosional dan Loyalitas Anggota di Komunitas Literasi Provinsi Gorontalo - Fahri Kamuli; Putu Regina Sanjiwani Prakasa; Wulandari Ney; Suci Nugrani (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Literacy communities in Gorontalo Province face persistent challenges in maintaining member engagement, particularly related to declining emotional bonds and loyalty among members. This study aimed to evaluate the effectiveness of a psychoeducational intervention designed to strengthen emotional bonds and loyalty among members within literacy communities across Gorontalo Province. Using a mixed-methods design, the program was preceded by a needs assessment conducted through in-depth interviews, which identified diverse professional backgrounds and inadequate bonds among members as key factors contributing to declining cohesion. The intervention was delivered as a seminar involving 40 participants representing 20 literacy communities (two delegates per community), held on September 30, 2025, at the Dulohupa Hall of the Gorontalo Provincial Language Office. Data were collected through pre-tests, post-tests, interviews, and documentation. Results showed a significant increase in participants' understanding of the material, with the average score increasing from 55.02 in the pre-test to 65.17 in the post-test, representing an increase of 10.15 points. Further qualitative findings demonstrated high participant engagement, as evidenced by active discussions and the exchange of practical strategies for strengthening community bonds. These findings suggest that the psychoeducational seminar approach is an effective and contextually appropriate method for building emotional bonds and loyalty within the volunteer literacy community. This intervention is expected to have multi-layered impacts, fostering individual competency and collective empowerment, thus contributing to the long-term resilience and sustainability of the literacy movement in Gorontalo Province